Supply, Demand, and In-Stream Retention of Dissolved Organic Carbon and Nitrate During Storms in Mediterranean Forested Headwater Streams - Bernal, Susana; Lupon, Anna; Wollheim, Wilfred M.; Sabater, Francesc; Poblador, Sílvia; Martí, Eugènia (Frontiers in Environmental Science, 2019)
The capacity of headwater streams to transform and retain organic matter and nutrients during base flow conditions has been largely demonstrated in the literature. Yet, most solute export occurs during storms, and thus, it becomes essential to understand the role of in-stream processes on regulating solute concentrations and exports during storm flow conditions. In this study, we explored patterns of solute supply, solute demand, and resulting in-stream solute retention for a number of individual storms from two Mediterranean streams (intermittent and perennial) that together encompassed a wide range of hydrological conditions. Our results indicate that >70% of the individual storms were chemodynamic (i.e. solute concentrations either increased or decreased with increasing discharge) at the two sites and for both dissolved organic carbon (DOC) and nitrate (NO3-). At the perennial stream, DOC and NO3- concentrations did not show any clear pattern of storm response during both dry and wet periods, though deviations from chemostasis were generally larger for those events showing higher concentrations during storm flow. At the intermittent stream, DOC and NO3- showed positive divergences from chemostasis during the wet period. In this site, DOC showed no clear pattern of storm response during the dry period, while many storms showed low NO3- concentrations compared to chemostasis, suggesting either limited NO3- sources or in-stream retention. At the two streams, in-stream biogeochemical demand during individual storms was either similar or higher than during base flow conditions for both DOC and NO3-. In-stream NO3- demand resulted in substantial whole-reach retention during storms (up to 40%), indicating that in-stream biogeochemical processes substantially reduced downstream flux of terrestrial NO3- inputs during storm events. Conversely, whole-reach DOC retention was relatively low during storms (< 10%), suggesting little ability to regulate DOC export and an energy subsidy to downstream ecosystems during storms. This study indicates that in-stream biogeochemical demand during storms can counterbalance solute supply to some extent, and stresses the importance of considering the potential role of in-stream processes on shaping stream solute export during storms.